Base-induced synthesis of N-dialkylaminomethyl-2H-1, 2, 3-triazoles from N-sulfonyl-1, 2, 3-triazoles. Issue 6 (15th April 2016) - Jiang, Yu; Wang, Qiang; Sun, Run; Tang, Xiang-Ying; Shi, Min
Abstract : A facile synthetic method to access N -dialkylaminomethyl-2 H -1, 2, 3-triazoles has been developed from N -sulfonyl-1, 2, 3-triazoles by a base induced reaction. Moreover, 4-phenyl-1 H -1, 2, 3-triazoles can also give the same product even in the absence of a base at high temperature. Abstract : A facile synthetic method to access N -dialkylaminomethyl-2 H -1, 2, 3-triazoles has been developed via a novel reaction mode from N -sulfonyl-1, 2, 3-triazoles by a base induced reaction. Moreover, 4-phenyl-1 H -1, 2, 3-triazoles can also give the same products even in the absence of a base at high temperature.